Assessing crops index number muddle - Khare, M.P. (1999)
An index number of agricultural growth is used for the overall assessment of agricultural growth. In Maharashtra an error was made in constructing the index number some 25 years ago, and has gone unnoticed. - Reproduced
Keywords: Agriculture - India; Agriculture